2009
DOI: 10.1097/coc.0b013e3181942a1f
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II Study of a Cisplatin-Taxol-Dacarbazine Regimen in Metastatic Melanoma

Abstract: Cisplatin-paclitaxel-dacarbazine regimen is effective in patients with advanced melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 15 publications
0
15
0
1
Order By: Relevance
“…trials were identified and reviewed. [9][10][11][12][13][14][15][16][17][18][19][20] These included 2 trials of neoadjuvant therapy for regional metastases, 1 trial of adjuvant therapy, and 9 trials for metastatic melanoma. We identified 330 (44%) patients who developed brain metastases at some point during the course of their disease.…”
Section: Resultsmentioning
confidence: 99%
“…trials were identified and reviewed. [9][10][11][12][13][14][15][16][17][18][19][20] These included 2 trials of neoadjuvant therapy for regional metastases, 1 trial of adjuvant therapy, and 9 trials for metastatic melanoma. We identified 330 (44%) patients who developed brain metastases at some point during the course of their disease.…”
Section: Resultsmentioning
confidence: 99%
“…TMZ, an oral alkylating agent, demonstrated a longer median progression-free survival (1.9 months) when compared with DTIC [1.5 months, P = 0.012, hazard ratio (HR) = 1.37, 95% confidence interval (CI) 1.07-1.75] [10], as well as comparable tolerability, although TMZ's improved progression-free or overall survival was not confirmed in other randomized phase 3 trials such as the European Organization for Research and Treatment of Cancer (EORTC) 18032 trial [11]. PAC administered as a single agent yielded overall response rates of 14-16%, whereas combined therapy with PAC and platinum-based agents had response rates ranging from 20 to 41% [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Remission rates range from 15 to 25% with a median survival of 7.8 months [16][17][18]. A similar combination to the one we presented of cisplatin, paclitaxel and DTIC was studied in 46 patients with metastatic melanoma [19]. The starting doses of the drugs in this regimen were intravenous cisplatin 20 mg/m 2 on days 1-4, intravenous paclitaxel 120 mg/m 2 on days 1 and 8, and intravenous DTIC 800 mg/m 2 on day 1.…”
Section: Discussionmentioning
confidence: 88%